Self-similarity of spanwise rotational motions' population trends in decelerating open-channel flow. Issue 3 (March 2022) - Zhang, Peng; Duan, Yanchong; Zhong, Qiang; Li, Danxun; Yang, Shengfa; Hu, Jiang; Li, Wenjie
Abstract: Decelerating open-channel flow is a type of flow that gradually moves forward with decreasing velocity and increasing water depth. Although all flow parameters change along the streamwise direction, previous studies have revealed that these parameters' vertical distributions at different sections can be universally described with a single profile when being nondimensionalised by appropriate scales. This study focuses on the population trends of spanwise rotational motions at various sections along the main flow direction by particle imaging velocimetry (PIV) measurement. The wall-normal population distributions of density, radius, swirling strength, and convection velocity of the prograde and retrograde motions show similar trends in uniform open-channel flows. The dimensionless representation is invariant along the main flow direction. This study's results indicate the self-similar characteristic of population trends of spanwise rotational motions prevails in decelerating open-channel flow.